New insights into microwave pyrolysis of biomass: preparation of carbon-based products from pecan nutshells and their application in wastewater treatment - Duran Jimenez, G.; Monti, Tamara; Titman, Jeremy J.; Hernandez-Montoya, V.; Kingman, S.W.; Binner, Eleanor (Elsevier, 2017)
Microwave pyrolysis of pecan nutshell (Carya illinoinensis) biomass was used to produce carbon-based solid products with potential application in contaminated water treatment.